2009
DOI: 10.1074/jbc.m109.024869
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine Activates Adipocyte Glucose Uptake and Lowers Blood Glucose Levels in Murine Models of Diabetes

Abstract: Glucose homeostasis is maintained by the orchestration of peripheral glucose utilization and hepatic glucose production, mainly by insulin. In this study, we found by utilizing a combined parallel chromatography mass profiling approach that lysophosphatidylcholine (LPC) regulates glucose levels. LPC was found to stimulate glucose uptake in 3T3-L1 adipocytes dose-and time-dependently, and this activity was found to be sensitive to variations in acyl chain lengths and to polar head group types in LPC. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 36 publications
7
91
0
Order By: Relevance
“…1A ; supplementary Table 1). A previous study reported that LPC(16:0) increased adipocyte glucose uptake ( 31 ). We confi rmed that plasma glucose was decreased (to ‫ف‬ 60% vs. control) by bezafi brate treatment ( Table 1 ).…”
Section: Lpc In Plasma Was Increased By Ppar ␣ Activationsupporting
confidence: 58%
See 2 more Smart Citations
“…1A ; supplementary Table 1). A previous study reported that LPC(16:0) increased adipocyte glucose uptake ( 31 ). We confi rmed that plasma glucose was decreased (to ‫ف‬ 60% vs. control) by bezafi brate treatment ( Table 1 ).…”
Section: Lpc In Plasma Was Increased By Ppar ␣ Activationsupporting
confidence: 58%
“…It is well recognized that LPC(16:0) increases adipocyte glucose uptake ( 31 ). We also confi rmed the LPC(16:0) capacity to promote glucose uptake in 3T3-L1 adipocytes in a dose-dependent manner and LPC(16:0) had an additive effect increasing glucose uptake in 3T3-L1 adipocytes cotreated with insulin and LPC(16:0) (data not shown).…”
Section: Lpc(16:0) Stimulates Glucose Uptake In Insulin-resistant 3t3supporting
confidence: 57%
See 1 more Smart Citation
“…For example, the activation of α 1 -adrenergic or endothelin A receptors results in enhanced glucose uptake rates independently of insulin levels, and physical exercise also plays an important role in the metabolism of glucose by skeletal muscle. Hence, exercise or drug-mediated glucose uptake, are therapeutic targets in type 2 diabetes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In adipose tissue, it has been shown that increases in specific LysoPC species 12:0, 16:0, and 18:0 caused an increase in the glucose 4 transporter and therefore increased glucose uptake in a dose dependant manner (Yea et al, 2009). These findings provide another example o f how changes in lipid profiles o f adipose tissue could result in impaired glucose uptake and therefore lead to hyperglycemia in patients with T2D.…”
Section: Lipid Profiles Of Islets Isolated From P-ppary2-hfd Micementioning
confidence: 99%